The Small GTPase Cdc42 Is a Major Regulator of Neutrophil Effector Functions - Tackenberg, Heidi; Möller, Sonja; Filippi, Marie-Dominique; Laskay, Tamás (Frontiers in Immunology, 2020)
Neutrophil granulocytes are key components of the innate immune system. As the first responders to inflammatory cues, they rapidly migrate towards the site of infection or inflammation and fulfill diverse effector functions. Since these effector functions can be both beneficial, and harmful to the host and surrounding tissue, they require a strict control. The small GTPase Cdc42 is known to regulate neutrophil locomotion by controlling cytoskeleton rearrangement in murine neutrophils. However, the role of Cdc42 in other neutrophil functions in human neutrophils is still poorly understood. Here we demonstrate that in primary human neutrophils, Cdc42 controls directed and random migration, activation and degranulation as well as the formation of reactive oxygen species, in a stimulus dependent manner. In addition, we show that Cdc42 regulates pathogen killing efficiency, both in murine and human neutrophils. Cdc42 regulation of neutrophil functions is linked to differential regulation of Akt, p38 and p42/44. Our data therefore suggests a mechanistic role for Cdc42 activity in primary human neutrophil biology, and identify Cdc42 activity as a target to modulate neutrophil effector mechanisms and killing efficacy.